GCA-EoS: A SAFT group contribution model-Extension to mixtures containing aromatic hydrocarbons and associating compounds - Sánchez, Francisco Adrián (2011)
GCA-EoS is the first equation of state that takes into account association using a SAFT-like group contribution term. It has been recently upgraded to deal simultaneously with multiple associating and solvating groups. In this work a review of applications and parameters revisions are presented and the GCA-EoS extension to aromatic hydrocarbons is discussed. These compounds are important in different industrial fields (textile, fine chemicals, pharmaceutical, petrochemicals, materials, etc.). Moreover, compounds like phenol play a major role not only in several polymers syntheses but also in biomass processing mixtures. Specifically, the extension to systems containing aromatic hydrocarbons (BETX and alkylbenzenes), water and alkanols is discussed.